2018
DOI: 10.4236/jss.2018.65009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HEdPERF on Students’ Satisfaction and Academic Performance in Ghanaian Universities; Mediating Role of Attitude towards Learning

Abstract: This study investigates the impact of HEdPERF on students' satisfaction and academic performance in Ghanaian private universities, with students' attitude towards learning as a mediator. The study was conducted on a total of 600 students selected from 6 private universities in Ghana out of which 421 responses received were useable representing 70.16% response rate. Purposive and convenience sampling techniques were adopted in selecting respondents. Questionnaire was used to collect data. Explanatory research d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 36 publications
7
16
0
1
Order By: Relevance
“…The results indicate that the combination of service quality dimensions, namely academic aspects, non-academic aspects, reputation, access, and program issues, significantly predicts students' satisfaction, as well. This result is similar to the following studies: Kajenthiran and Karunanithy (2015), Truong et al (2016), Baniya (2016), Azam (2018), Banahene et al (2018), andMuhammad et al (2018). Yet it is contrary to the following studies: Osman and Saputra (2019) and Dib and Alnazer (2013).…”
Section: Conclusion and Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results indicate that the combination of service quality dimensions, namely academic aspects, non-academic aspects, reputation, access, and program issues, significantly predicts students' satisfaction, as well. This result is similar to the following studies: Kajenthiran and Karunanithy (2015), Truong et al (2016), Baniya (2016), Azam (2018), Banahene et al (2018), andMuhammad et al (2018). Yet it is contrary to the following studies: Osman and Saputra (2019) and Dib and Alnazer (2013).…”
Section: Conclusion and Discussionsupporting
confidence: 84%
“…Yet it is contrary to the following studies: Osman and Saputra (2019) and Dib and Alnazer (2013). The results indicate that 'academic aspects' are a predictor of students' satisfaction and support the following studies: Việt (2021), Ali et al (2020), Azam (2018), Banahene et al (2018), andMuhammad et al (2018). This result may be attributed to students' belief of the importance of academic staff's role in enhancing their knowledge and preparing them for job market or developing their career skills.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Through the first research hypothesis, it was shown that there is a significant and positive relationship between the perceived quality of educational services proposed by the HEdPERF model and student satisfaction, as evidenced by previous studies Banahene et al, 2018;. On the other hand, regarding the second research hypothesis, it was also demonstrated that there is a significant and positive relationship between each of the six dimensions and student satisfaction.…”
Section: Discussionsupporting
confidence: 56%
“…As as result of the literature review, it is seen that the number of studies using HEdPERF scale is increasing day by day (Ali, Shariff, Said & Mat, 2018;Ali et al, 2016;Ada, Baysal & Erkan, 2017;Banahene, Kraa & Kasu, 2018;Damaris, Surip & Setyadi, 2019;Deveci & Aymankuy, 2017;Firdaus, 2006;Firdaus, 2019;Khalid, Ali & Makhbul, 2019;Lazibat et al, 2014;Mang'unyi & Govender, 2014;Mekic & Mekic, 2016;Muhammad, Kakakhel, Baloch & Ali, (TKA, 2010: 5-73;TKA, 2013: 19-89). This study is intended to identify how tourism students at these three aforementioned universities view the service quality of institutions of higher education.…”
Section: Methodsmentioning
confidence: 99%